(untitled) (Journal of Engineering, 2024)
Finding an alternative to materials that pollute during manufacturing, most notably cement, is vital to executing the idea of sustainability in the building sector. It was vital to develop concrete that assists in the reduction of CO2 (Carbon dioxide) in the atmosphere because industrial wastes contain calcium, silica, and aluminous minerals, such as silica fume, that are employed in the production of high-strength concrete and have parameters that are identical to those of regular concrete. As a substitute for Portland cement, lime cement was utilized, and 15% of the cement’s weight was substituted with silica fume. Environmentally friendly fibers (Copper Fiber) created from old electrical and electronic equipment were also employed. The purpose of the study is to produce High Strength Green Fiber Concrete (HSGFC) by incorporating silica fume as a replacement and study the effect of adding fiber on some mechanical attributes. The task needed the creation of a high strength concrete mixture of cement with a compressive strength of 65 MPa in accordance with ACI 211.4R, as well as the development of numerous experimental mixtures that relied on the findings of earlier researchers. The mechanical properties (compressive strength, flexural strength and split tensile strength) of samples are tested at 7, 28 and 60 days with standard curing. The results show that adding sustainable fiber to concrete mix enhances the mechanical properties such as compressive strength by 16% at 28 days, flexural strength by 35% and spilt tensile strength by 44% at 28 days Compared with concrete mix with no fiber. Also, the outcomes showed that it is feasible to develop High Strength Concrete (HSC) using sustainable copper fiber possessing exceptional stress resistance, tensile strength, and flexural strength.